Integrating Social Media Marketing and Brand Gestalt: An Empirical Analysis in Educational Institutions - Pasuhuk, Lefrand S.; Mandagi, Deske W (LP. Ma'arif Janggan Magetan, 2023)
This study endeavors to assess the effectiveness of Social Media Marketing (SMM) on the brand gestalt of educational institutions, with a specific focus on universities. In particular, the research aims to examine the impact of SMM on 4S dimensions of brand gestalt: story, sensescape, servicescape, and stakeholders. The research design employed is descriptive causal, utilizing primary data collected through a survey of 209 samples consisting of private university students in North Sulawesi, Indonesia. Data analysis was carried out using Structural Equation Modeling (SEM), supported by the SmartPLS statistical program. The results of the analysis reveal a positive and significant influence of SMM on all four dimensions of brand gestalt: story, sensescape, servicescape, and stakeholders. These findings shed light on the crucial role of social media in shaping robust brand perceptions.